Tricaine methane-sulfonate (MS-222) application in fish anaesthesia - Topic Popovic, N.; Strunjak-Perovic, I.; Coz-Rakovac, R.; Barisic, J.; Jadan, M.; Persin Berakovic, A.; Sauerborn Klobucar, R. (Journal of applied ichthyology, 2012)
Summary Tricaine methane‐sulfonate (MS‐222) is one of the most widely used anaesthetics for poikilotherms worldwide. This paper outlines its anaesthetic efficacy and dosage in fish and legislation for its use, fish stress responses to MS‐222 anaesthesia and its effect on fish physiology and blood properties, pharmacokinetics, genotoxicity, immune response, potential interference with fish hepatic cytochrome P450 spectra, and its impact on nerve sensitivity. Key questions arising from the available data are analysed, such as regulatory constraints on its use, the need for the standardization of buffering protocols, and interdependencies of the factors impacting the specific applicative efficacy of MS‐222. Current research has provided an abundance of data on MS‐222 use in fish, although the applications within these studies are often impractical at the farming level. Specific emphasis is therefore placed on highlighting application strategies on a practical basis, presenting potential future research on topics that require in‐depth analysis (preparation and storage of anaesthetic solutions, pre‐anaesthetic sedation and stress reduction, cortisol response in aquarium fish, toxicity of MS‐222 metabolites, and possible immunodepressive properties). Additionally, both from a scientific and practical perspective, it is necessary to have a better understanding of safety margins, induction, immersion and recovery times for many (marine and freshwater, farmed and ornamental) fish species in order to achieve optimal utilization.